Hungarian Monitoring, 4 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Wave of strikes in Poland - Reactions abroad to Romanian-Hungarian meeting - Le Pen's antisemitic remarks Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) makes contact with Hungarian Democratic Forum (MDF) - Tense Romanian-Hungarian situation - Conference on Danube dams urges stopping Gabčíkovo-Nagymaros construction - President of State Churches' Office travels to Israel - Dialogue between believers and Marxists Külpolitika - Sztrájkhullám Lengyelországban - A román-magyar találkozó külföldi visszhangja - Le Pen antiszemita megnyilvánulása Belpolitika: - Az MSZMP felvette a kapcsolatot az MDF-el - Feszült román-magyar helyzet - A dunai vízlépcsőkről folyó tanácskozás a bős-nagymarosi építkezés leállítását sürgeti - Izraelbe utazott az Állami Egyházügyi Hivatal elnöke - Hívők és marxisták párbeszéde